Bacteria communities of coffee plant rhizosphere and their potency as plant growth promoting (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Suharjono, Yuliatin E. 2022. Bacteria communities of coffee plant rhizosphere and their potency as plant growth promoting. Biodiversitas 23: 5822-5834. This study aimed to investigate the soil bacteria communities of the coffee rhizosphere and evaluate the potency in supporting coffee plant growth. The soil was collected from the Coffea canephora and Coffea arabica in Malang, East Java. The bacterial genomic DNA was extracted by FastDNA Spin kit while the Illumina platform analyzed the total gDNA. Other samples were isolated using the serial dilution method on Tryptic Soy Agar, Pikovskaya Agar, and Nitrogen-free-Bromothymol Blue Agar medium to isolate IAA-producing, phosphate-solubilizing, and nitrogen-fixing bacteria, respectively. The selected bacteria isolates were identified based on 16S rDNA sequencing. As a result, the Proteobacteria showed dominance at the phyla level, and Bradyrhizobium elkanii was the most abundant species with a not significant different proportion between Robusta and Arabica soil. The quantifying method of the selected isolate showed the maximum concentration, such as S1.6.3.2 isolate producing IAA-hormone at 104.46 µg/mL, W3.5 isolate solubilizing the phosphate at 4.5 µg/mL, and W1.2 isolate fixing the ammonia at 21.54 µg/mL. Those potential isolates, S1.6.3.2, W3.5, and W1.2, were identified as Bacillus subtilis DSM 10, Pseudomonas putida S18, and Bacillus methylotropicus SY2, respectively. Further research shows that those bacteria consortiums can be a candidate as biofertilizers due to helping soil health stimulation and promoting coffee growth.
Keywords: Bradyrhizobium, coffee, genomic, rhizosphere, soil